Carbon material/vitrimer composites: Towards sustainable, functional, and high-performance crosslinked polymeric materials. (March 2023) - Wu, Yahe; Wei, Yen; Ji, Yan
Abstract: Thermosets and their composites have occupied a key place in the polymeric material industry for both plastics and rubbers. Carbon material/thermoset composite is a major category thereof. The addition of carbon material (such as carbon fibers, carbon nanotubes (CNTs), and graphene) endows polymeric materials with better mechanical properties, enhanced optical and electrical properties, etc. However, due to the thermoset nature, the covalently crosslinked network brings huge reprocessing and recycling difficulties. The development of vitrimers paves a new way to produce recyclable and degradable thermosets. A series of carbon material/vitrimer composites have also been innovated, aiming at sustainable high-performance materials with better physical properties, recyclability, reprocessablity, and other novel stimuli-responsive functions. This review summarized the progress of carbon material/vitrimer composites in the past decade. A general introduction of vitrimer and the preparation strategies of different kinds of carbon material/vitrimer composites are given at first. Because of the vitrimeric nature, the service life of those composites could be significantly prolonged by reprocessing, healing, and recycling, the related strategies of which are described and summarized in detail. Then, the improved properties and new functions enabled by the incorporation of fillers are also overviewed. Our outlook on the future directions of carbon material/vitrimer composites is present at the end. Graphical abstract: Image, graphical abstract